Healing not punishment: historical and pastoral implications of the penitentials as observed in ecclesiastical networking between the sixth and the eighth centuries - Kursawa, Wilhelm (2017)
Although the advent of the Kingdom of God in Jesus contains as an intrinsic quality the opportunity for repentance (μετάνοια) as often as required, the Church of the first five-hundred years shows serious difficulties with the opportunity of conversion after a relapse in sinning after baptism. The Church allowed only one chance of repentance. Requirement for the reconciliation were a public confession and the acceptance of severe penances, especially after committing the mortal sin of apostasy, fornication or murder. As severe as this paenitentia canonica appears, its entire conception especially in the eastern part of the Church, the Oriental Church, is a remedial one: sin represents an ailment of the soul, the one, who received the confession, is called upon to meet the confessing person as a spiritual physician or soul-friend. Penance does not mean punishment, but healing like a salutary remedy. Nevertheless the lack of privacy led to the unwanted practice of postponing repentance and even baptism on the deathbed. An alternative procedure of repentance arose from the sixth century onwards in the Irish Church as well as the Continental Church under the influence of Irish missionaries and the South-West-British and later the English Church (Insular Church). In treatises about repentance, called penitentials, ecclesiastical authorities of the sixth to the eight centuries wrote down regulations, how to deal with the different capital sins and minor trespasses committed by monks, clerics and laypeople. Church-representatives like Finnian, Columbanus, the anonymous author of the Ambrosianum, Cummean and Theodore developed a new conception of repentance that protected privacy and guaranteed a discrete, an affordable as well as a predictable penance, the paenitentia privata. They not only connected to the therapeutic aspect of repentance in the Oriental Church by adopting basic ideas of Basil of Caesarea and John Cassian, they also established an astonishing network in using their mutual interrelations. Here the earlier penitentials served as source for the later ones. But it is remarkable that the authors in no way appeared as simple copyists, but also as creative revisers, who took regard of the pastoral necessities of the entrusted flock. They appeared as engaged in the goal to improve their ecclesiastical as well as their civil life-circumstances to make it possible that the penitents of the different ecclesiastical estates could perform their conversion and become reconciled in a dignified way. The aim of the authors was to enable the confessors to do the healing dialogue qualitatively in a high standard; quantity was not their goal. The penitents should feel themselves healed, not punished.